A pH‐Switchable Aqueous Organocatalysis with Amphiphilic Secondary Amine–Porphyrin Hybrids. Issue 28 (3rd July 2020) - Arlegui, Aitor; Torres, Pol; Cuesta, Victor; Crusats, Joaquim; Moyano, Albert
Abstract : A series of amphiphilic 5‐(cyclic‐secondary‐amine)‐10, 15, 20‐tris(4‐sulfonatophenyl)porphyrins, designed with the aim of using the amphiphilic porphyrin moiety for the modulation of the aggregation state of the compound by the pH of the medium, have been synthesised, and the relationship between their supramolecular behaviour in acidic aqueous media and their organocatalytic activity in Michael and aldol reactions has been investigated. In particular, we have found that the catalytic activity of the pyrrolidine moiety in an amphiphilic isoindoline–porphyrin hybrid for the aldol reaction of cyclohexanone with 4‐nitrobenzaldehyde can be selectively and reversibly switched on and off by adjusting the homogeneity of its solutions through pH variations. The catalysis of the aldol reaction by the secondary amine moiety would otherwise take place regardless of the pH of the medium. We have demonstrated that the aggregation behaviour of these amine–porphyrin hybrids can be also used for the recovery and reutilization of the catalysts. Abstract : A pH‐sensitive "Ampelmännchen": The catalytic activity of an amphiphilic isoindoline–porphyrin hybrid for the aqueous aldol reaction can be selectively and reversibly switched on and off . In neutral solutions the anionic form of the hybrid is highly soluble, allowing aminocatalysis to take place, whereas in acidic pH the protonated porphyrin core of the hybrid affords a highly insoluble, catalytically inactive J‐aggregate.